Volume Measurements on Weightbearing Computed Tomography Can Detect Subtle Syndesmotic Instability. Issue 1 (January 2022) - Ashkani-Esfahani, Soheil; Bhimani, Rohan; Lubberts, Bart; Kerkhoffs, Gino; Waryasz, Gregory R.; DiGiovanni, Christopher W.; Guss, Daniel
Category: Ankle; Trauma Introduction/Purpose: The ability to compare the ankle joints bilaterally in a 3D manner under physiologic weight provided by weight-bearing CT has led to a more accurate diagnostic method. While weight-bearing computed tomography (WBCT) allows 3D visualization of the distal syndesmosis, image interpretation has largely relied on 1D distance and, more recently, 2D area measurements. This study aimed to: 1) determine the sensitivity and specificity of 2D area and 3D volume WBCT measurements towards detecting subtle syndesmotic instability, 2) evaluate whether the patterns of changes in the 3D shape of the syndesmosis can be attributed to the type of ligament injury. Methods: A total of 24 patients with unilateral subtle syndesmotic instability and 24 individuals with uninjured ankles (controls) with bilateral ankle WBCT were assessed retrospectively. First, 2D areas at 0, 1, 3, 5, 10 cm, and 3D volumes at 1, 3, 5, and 10cm above the tibial plafond were measured bilaterally. Secondly, given the volume measurement at the level of 5 cm proximal to the platform as the most sensitive and specific method introduced in this study, the 3D model of the distal tibiofibular space was created based on WBCT in a subset of 8 patients out of 24 in whom the type of ligament injury was recognized via MRI. The 3D model of the injured side was superimposed on the uninjured contralateral side to visualize the pattern of changes in different planes. P<0.05 was considered statistically significant. Results: No specific pattern was observed in 2D and 3D models of the syndesmotic space which can be attributed to a specific ligamentous tear. However, in patients with IOL rupture, the volume increased by >=39% at 5 cm height while without IOL injury the volume increased up to 26% (figure 1). The percentage of changes in 2D areas and 3D volumes showed significant differences in areas at 0cm (19.2%; p=0.004), 1cm (24.1%; p=0.002), 3cm (27.3%; p=0.003), 5cm (28%; p=0.002), and 10cm (29.3%; p=0.003) as well as volumes at 1cm (31.2%; p=0.003), 3cm (26.5%; p=0.001), 5cm (25.4%; p<0.001), and 10cm (24.7%; p=0.004) proximal to tibial plafond. Volume up to 5cm showed the lowest p-value, higher sensitivity (95.8%, 95%CI:87.8-100), and specificity (83.3%, 95% CI:68.4-98.2) for detection of syndesmotic instability. Conclusion: We suggest 3D volume measurements, best measured up to 5cm proximal to the plafond, as a promising means of diagnosing syndesmotic instability, particularly for subtle cases that are hard to detect.